The Argument(s) for Universal Gravitation - Ducheyne, Steffen (Foundations of Science, 2006)
In this paper an analysis of Newtons argument for universal gravitation is provided. In the past, the complexity of the argument has not been fully appreciated. Recent authors like George E. Smith and William L. Harper have done a far better job. Nevertheless, a thorough account of the argument is still lacking. Both authors seem to stress the importance of only one methodological component. Smith stresses the procedure of approximative deductions backed-up by the laws of motion. Harper stresses systematic dependencies between theoretical parameters and phenomena. I will argue that Newton used a variety of different inferential strategies: causal parsimony considerations, deductions, demonstrative inductions, abductions and thought-experiments. Each of these strategies is part of Newtons famous argument.
Keywords: argumentative pluralism; Newton; Principia; Universal gravitation